Elements of indigenous cultural resistance in a dramatic play for evangelization. T’ikahina of the priest Nemesio Zúñiga Cazorla - Jofré Seguel, Ilsen Alejandra (2019)
T’ikahina is drama from 1920 (estimated date) written by Nemesio Zuñiga Cazorla a priest of Quechua origin. The play is located in Peru during the Colony and tells the history of a nobel family from Cusco and the conflict between the ancient traditions and the rising christian culture. As it was done in the Americas since the times of the Conquest, Zuñiga utilizes drama as a bridge to spread out the góspel and includes a variety of elements from the pre-Hispanic culture. The author refers to everyday situations and ritual ceremonies with an outstanding use of a language plenty of poetry, conventional greetings and indigenous origin vocabulary.